Aquaculture Production and Value Chains in the COVID-19 Pandemic - Nesar Ahmed; Mohamad N. Azra (Current Environmental Health Reports, 2022)
Purpose of Review The purpose of this review is to summarize the impacts of the coronavirus disease 2019 (COVID-19) pandemic on aquaculture input supply, production, distribution, and consumption. Recent Findings The COVID-19 pandemic–related lockdowns, social distancing, supply chain disruptions, and transport restrictions affect seafood production, distribution, marketing, and consumption. Recommendations are suggested to overcome these challenges. Summary The COVID-19 has led to disruption of aquaculture practices worldwide. The pandemic has adversely affected the aquaculture input supply of fish stocking and feeding, which, in turn, has impacted aquaculture production. Moreover, the COVID-19 crisis has had adverse effects on value addition to aquaculture products, through the restrictions of seafood marketing and exporting. Aquatic food production is vulnerable to the effects of COVID-19 outbreak; hence, adaptation strategies must be developed to cope with the challenges. There is an urgent need for collaboration among key stakeholders to rebuild the supply chain of inputs and fish marketing for sustainable aquaculture practices. International agencies, donors, government and non-governmental organizations, researchers, and policymakers need to develop policies to support aquaculture production and supply chains.